Reviews of new publications - Holmes, Derek A (KUKILA, 1989)
MacKinnon, J. 1988. Field guide to the birds of Java and Bali. Jogyakarta:Gadjah Mada University Press. Holmes, D.A. and Nash, 8.V. 1989. The Birds of Java and Bali. Singapore: Oxford University Press. Lambert, F. 1988. Th» status of the White-winged Wood Duck in Sumatra, Indonesia: a preliminary assessment. PHPA-AWB/Interwader Report No. 4. Erftemeijer, P. & Edi Djuharsa. 1988. Survey of coastal wetlands and waterbirds in the Brantas and Solo Deltas, East Java (Indonesia). PHPAAWB/Interwader Report No. 5, Bogor Erftemeijer, P., Bas van Ba1en Edi Djuharea. 1988. The importance of Segara Anakan for nature conservation, with special reference to its avifauna. PHPA-AWB/INTERWADER Report No. 6, Bogor.